Rancang Bangun Timbangan Digital Berbasis Mikrokontroler dan IoT untuk Peternakan Domba - Ulfa, Afrida Nurul; Isnianto, Hidayat Nur (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2023)
This study developed an integrated digital scale with a microcontroller and an Internet of Things feature that weighs the sheep and measures its temperature. It is composed of a scale frame, two alternative power supplies, namely a 12 V battery and 24 V PSU, a component box containing a temperature sensor, load cell module, Arduino Mega 2560 microcontroller with built-in Wi-Fi ESP8266, equipped with an LCD user interface, RFID reader and thermal gun. The sheep were assigned their respective RFID IDs to enable detection by the RFID reader. When sheep walked into the core frame of the scales, the sheep ID appeared on the LCD. The load cell sensor automatically weighed the sheep. Simultaneously, the temperature data was displayed on the LCD and sent to the server when the user aimed the thermal gun at the sheep rectum. The weight measurement has been tested on live sheep. The accuracy of weight measurement was compared with a conventional standard scale. The system's RFID reader detected the Tag RFID within the 0—75 cm range. Thermal sensor MLX90614 measured the temperature with the lowest accuracy of 99,69% and the highest accuracy of 99,97%. The Flintec load cell PB 3.75–375 measured the sheep's weight with the lowest accuracy of 98,28% and the highest accuracy of 99,92%.